The Enormous Vogue of Things Mexican : Cultural Relations between the United States and Mexico, 1920-1935. - Delpar, Helen (University of Alabama Press, 2015)
Beginning about 1900 the expanded international role of the United States brought increased attention to the cultures of other peoples and a growth of interest in Latin America. The Enormous Vogue of Things Mexican traces the evolution of cultural relations between the United States and Mexico from 1920 to 1935, identifying the individuals, institutions, and themes that made up this fascinating chapter in the history of the two countries.